Efficacy of Endoscopic Recalanalization of the Urethra in Men - S. S. Kasimov; E. R. Navruzov (Scholars Digest Publishing, 2023)
The article summarizes the results of the analysis of data from the treatment of 53 patients who underwent endoscopic recanalization of the obliterated urethra, followed by electroresection of scar tissue. Conducted clinical studies have shown that relapses after the intervention, by the end of 1 year of observation, occur in 18.9% of patients.
Keywords: urethral obliteration, endoscopic treatment, efficacy, stricture recurrence.